Coefficient Estimates for a Class of $m$-Fold Symmetric Bi-Univalent Function Defined by Subordination (Communications in Mathematical Research, 2020)
In this paper, we investigate the coefficient estimates of a class of $m$-fold bi-univalent function defined by subordination. The results presented in this paper improve or generalize the recent works of other authors.